Enforcing obligations erga omnes in international law - Tams, Christian J. (Cambridge, UK ; New York : Cambridge University Press, 2005)
The concept of obligations erga omnes - obligations to the international community as a whole - has fascinated international lawyers for decades. This book shows how this highly controversial concept has become part of modern-day international law, and how it will enhance human rights in the future.
Cover; Half-title; Series-title; Title; Copyright; Contents; Foreword; Preface; Notes on citation; Table of cases; Abbreviations; Introduction; PART I BACKGROUND TO THE ERGA OMNES CONCEPT; PART II LEGAL ISSUES RAISED BY THE ERGA OMNES CONCEPT; Conclusion; Bibliography; Index.
Includes bibliographical references (pages 312-350) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: International obligations; International law -- Moral and ethical aspects; Customary law, International; Obligations internationales; Droit coutumier international; POLITICAL SCIENCE -- International Relations -- Treaties; Customary law, International; International law -- Moral and ethical aspects; International obligations